Challenges and Considerations in Assessing Healthcare Service Quality: A Comprehensive Analysis - Willie, Michael Mncedisi (Manunggal Halim Jaya, 2024)
Service quality is vital in determining customer satisfaction and loyalty across industries. This paper comprehensively reviews service quality as a mediator variable, synthesising existing literature on its theoretical underpinnings, empirical evidence, and practical implications. Traditional service quality dimensions like reliability and responsiveness are discussed alongside emerging dimensions like accessibility and communication. The application of the SERVQUAL model across different industries is examined, highlighting its utility and addressing limitations, particularly in healthcare. Challenges related to standardisation, intangible aspects of care, limited scope, dynamic care delivery, biases in patient responses, lack of generalizability, and contextual factors in telemedicine are discussed. Tailored approaches considering industry-specific dynamics and customer needs are recommended to enhance service quality assessment and management.